Codimension two HOPF bifurcations in a model for Langmuir calculations. - Moroz, I; Leibovich, S (Pergamon Press, 1988)
Considers Langmuir circulations, a system of counter rotating vortices which develop in the surface layer of oceans and lakes for sufficiently strong winds, and discusses behaviour in the neighbourhood of the point where two oscillatory modes are simultaneously excited. Uses the method of multiple scales to develop nonlinear evolution equations for the amplitudes of the growing modes. Describes the unfolding of the bifurcation. Regions with single frequency oscillation and quasi periodic flow appear to occur.